Creating A Grounded Theory On Acquiring English Reading Skills: Perspectives From Learner Experiences And Cognitive Approaches - Ismail, Hijril; Jasin, Hamida A.; Asbah; Edi; Lukman; Ariyani, Etika (Arden Jaya Publisher, 2025)
Despite a wealth of research on the acquisition of English reading skills, few studies have focused on the process from the perspective of learners’ experiences and cognitive strategies, especially within an English as a Foreign Language (EFL) context. A significant portion of existing research relies on established models rather than extracting insights directly from students, which creates a gap in understanding the development of reading proficiency in actual academic environments. This study seeks to create a grounded theory of English reading skill acquisition by exploring the experiences, challenges, and strategies of EFL learners. Utilizing a constructivist grounded theory methodology, data was gathered via semi-structured interviews with thirty undergraduate students across various proficiency levels (beginner, intermediate, and advanced) and ten English language instructors. The analysis employed the constant comparative method, which included open coding to identify themes, axial coding to recognize relationships, and selective coding to construct a theoretical framework. Results indicate that students face obstacles such as limited vocabulary, complicated sentence structures, cultural unfamiliarity, and reading anxiety, while utilizing strategies like skimming, scanning, predicting meanings, summarizing, and applying translation tools. Instructors highlight the necessity of explicit instruction in reading strategies and scaffolding techniques to aid learners. The study concludes that effective reading instruction should combine strategy-based learning with techniques to alleviate anxiety, ensuring that teaching methods are in tune with students’ cognitive processes to improve reading proficiency in higher education EFL settings